Scarcity and Cooperation: The Modulation of Social Norms - Qiuling Luo; Changjin Qiu; Sihan Dong; Ronghui Tang; Chunhua Kang (Behavioral Sciences, 2025)
Given the continued relevance of perceived scarcity, understanding how a scarcity mindset influences human cooperation remains critical. However, previous research has yielded mixed results regarding this relationship. To clarify these inconsistencies, this study examined the impact of a scarcity mindset on cooperation within various social normative contexts. Participants were randomly assigned to either a scarcity or abundance mindset and engaged in a Public Goods Game under descriptive or injunctive normative conditions, each with high or low prosocial expectations. The results revealed that in both normative contexts, individuals with a scarcity mindset exhibited greater cooperation than those with an abundance mindset. Individuals also cooperated more under high prosocial norms compared to low ones. Importantly, the interaction effect revealed that while cooperation did not differ between the two mindsets under low prosocial norms, the scarcity mindset led to significantly greater cooperation under high prosocial norms. These findings provide new insights into the scarcity–cooperation dynamic and suggest that robust prosocial norms can amplify the cooperative tendencies associated with a scarcity mindset, highlighting the importance of leveraging social norms to enhance cooperation in resource-scarce situations.